2010
DOI: 10.1039/c0sm00132e
|View full text |Cite
|
Sign up to set email alerts
|

Buckled in translation

Abstract: We report experiments on the deformation and transport of an elastic fiber in a viscous cellular flow, namely a lattice of counter-rotative vortices. We show that the fiber can buckle when approaching a stagnation point. By tuning either the flow or fiber properties, we measure the onset of this buckling instability. The buckling threshold is determined by the relative intensity of viscous and elastic forces, the elasto-viscous number Sp. Moreover we show that flexible fibers escape faster from a vortex (forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
69
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 17 publications
12
69
1
Order By: Relevance
“…Beyond a critical tension (or flow velocity) there is a bifurcation to a buckled state, which then proceeds to rotate and stretch out along the extensional direction. Experiments on macroscopic fibres (Wandersman et al 2010) confirmed the details of this process, but left unexplored the important role of noise in a microscale realization of the instability. This experiment used the crosschannel microfluidic set-up in figure 6 within which were held individual fluorescently labelled actin filaments (Kantsler & Goldstein 2012).…”
Section: Cytoplasmic Streamingmentioning
confidence: 77%
“…Beyond a critical tension (or flow velocity) there is a bifurcation to a buckled state, which then proceeds to rotate and stretch out along the extensional direction. Experiments on macroscopic fibres (Wandersman et al 2010) confirmed the details of this process, but left unexplored the important role of noise in a microscale realization of the instability. This experiment used the crosschannel microfluidic set-up in figure 6 within which were held individual fluorescently labelled actin filaments (Kantsler & Goldstein 2012).…”
Section: Cytoplasmic Streamingmentioning
confidence: 77%
“…Evolution of their nonstraight shapes is related to the existence of a family of modes, which are activated if the characteristic parameter exceeds subsequent threshold values. The parameter is determined as the ratio of the viscous forces to the bending ones [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Dynamics of flexible fibers in simple shear and Poiseuille flows has been analyzed theoretically, numerically and experimentally in numerous publications [1][2][3][4][5][6][7][8][9][10][11][12]. Migration of fibers or vesicles in Poiseuille flow [13][14][15][16][17][18][19] is the fundamental problem of modern lab-on-chip hydrodynamics, important in various biological, medical and industrial contexts, such as Brownian dynamics of proteins, actins, DNA or biological polymers, cell motion, swimming of microorganisms, drug delivery, transport of microparticles [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The junctions at which a given single-stranded tile connects with two neighboring tiles are flexible, allowing the tube to crumple and then straighten when the compressive forces are relieved. This collapse into a coil configuration followed by stretching has been studied for other stiff linear biopolymers and synthetic fibers in hydrodynamic flows near stagnation points (33,37,38). Generally, the tubes will crumple under the compressive flow and reorient and stretch along the axis of the elongational flow (Movie S1 and SI Appendix, section 10).…”
Section: Significancementioning
confidence: 99%